2015
DOI: 10.3389/fmicb.2015.00736
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of pathogenic and non-pathogenic Vibrio parahaemolyticus in mollusks from the Spanish Mediterranean Coast

Abstract: Vibrio parahaemolyticus is a well-recognized pathogen of humans. To better understand the ecology of the human-pathogenic variants of this bacterium in the environment, a study on the prevalence in bivalves of pathogenic variants (tlh+ and tdh+ and/or trh+) versus a non-pathogenic one (only tlh+ as species marker for V. parahaemolyticus), was performed in two bays in Catalonia, Spain. Environmental factors that might affect dynamics of both variants of V. parahaemolyticus were taken into account. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Although Vibrio seems to be an important pathogenic agent in the NW Mediterranean (e.g. Canigral et al 2010, Lopez-Joven et al 2015, to the best of our knowledge no information on abundance of planktonic Vibrio (using culture independent methods) is available for Mediterranean waters.…”
Section: Introductionmentioning
confidence: 99%
“…Although Vibrio seems to be an important pathogenic agent in the NW Mediterranean (e.g. Canigral et al 2010, Lopez-Joven et al 2015, to the best of our knowledge no information on abundance of planktonic Vibrio (using culture independent methods) is available for Mediterranean waters.…”
Section: Introductionmentioning
confidence: 99%
“…Among the few reports, this is the case of the multiyear study performed on different shellfish, including R. philippinarum (120 samples) harvested in the Ebro Delta, Spain, from 2006 to 2010 (Lopez-Joven et al , 2014, 2015), but our results are not in agreement, because we found an higher prevalence of total V. parahaemolyticus (29.8 vs 14.2%) and potentially pathogenic V. parahaemolyticus (6.7 vs 3.3%), but a lower prevalence of total V. vulnificus (11.5 vs 22.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable improvements have been made in detecting V. parahaemolyticus in samples over the past two decades because of technological advancements. However, the detection of V. parahaemolyticus in samples is affected by numerous factors, including the substrate used for isolation, isolation methods, detection methods, and sampling period (Anupama et al., 2019; Givens et al., 2014; Lopez‐Joven, de Blas, Furones, & Roque, 2015; Pinto, Terio, Novello, & Tantillo, 2011). For example, the use of the chromogenic medium (CHROMagar Vibrio or Bio‐Chrome Vibrio medium) was found to be more effective than that of thiosulfate citrate bile salts sucrose (TCBS) agar for isolating colonies of V. parahaemolyticus (Duan & Su, 2005a; Pinto et al., 2011).…”
Section: Distribution Of V Parahaemolyticus In Oystersmentioning
confidence: 99%
“…Table 1 shows examples of studies that have investigated the presence of V. parahaemolyticus in oysters collected from either culturing environments or markets in either tropical, subtropical, or temperate areas. Oyster samples collected from tropical or subtropical areas (Cook et al., 2002; Deepanjali et al., 2005; DePaola, Nordstrom, Bowers, Wells, & Cook, 2003; Han et al., 2017; Johnson et al., 2010, 2012; López‐Hernández, Pardío‐Sedas, Lizárraga‐Partida, Williams, Martínez‐Herrera, Flores‐Primo, Uscanga‐Serrano, & Rendón‐Castro, 2015; Matté, Matté, Rivera, & Martins, 1994; New et al., 2014; Sanjeev & Stephen, 1993; Sobrinho et al., 2010, 2011; Ward & Bej, 2006; Yang et al., 2017; Yu et al., 2013, 2016; Zimmerman et al., 2007) are generally considered to exhibit higher concentrations of V. parahaemolyticus than those obtained from temperate areas (Cruz et al., 2015; Duan & Su, 2005b; Fletcher, 1985; Jones et al., 2014; Kaysner, Abeyta, Stott, Krane, & Wekell, 1990; Kaysner, Abeyta, Stott, Lilja, & Wekell, 1990; Kirs et al., 2011; Lopatek, Wieczorek, & Osek, 2015; Lopez‐Joven et al., 2015; Mok et al., 2019; Nakaguchi, 2013; Park, Mok, et al., 2018; Parveen et al., 2008; Roque et al., 2009; Ryu, Mok, Lee, Kwon, & Park, 2019; Tepedino, 1982; Thomson & Thacker, 1972). For example, concentrations of V. parahaemolyticus in oysters were 94% in India, between 77% and 100% in Brazil, 100% in Mexico, and 71% in Taiwan.…”
Section: Distribution Of V Parahaemolyticus In Oystersmentioning
confidence: 99%
See 1 more Smart Citation